Education and Training Research in Francophone Africa: Current Issues and Future Perspectives - (:unkn) unknown (My University, 2023)
Francophone Africa, at the intersections of diverse historical, cultural and social trajectories, is a crucible of innovations and questioning in education and training. This issue 69 of Éducation et socialisation, which we present here, is part of this dynamic, highlighting current and future issues through four major contributions.
Keywords: African Research